2008
DOI: 10.4049/jimmunol.180.5.3485
|View full text |Cite
|
Sign up to set email alerts
|

Etk/BMX, a Btk Family Tyrosine Kinase, and Mal Contribute to the Cross-Talk between MyD88 and FAK Pathways

Abstract: MyD88 and focal adhesion kinase (FAK) are key adaptors involved in signaling downstream of TLR2, TLR4, and integrin α5β1, linking pathogen-associated molecule detection to the initiation of proinflammatory response. The MyD88 and integrin pathways are interlinked, but the mechanism of this cross-talk is not yet understood. In this study we addressed the involvement of Etk, which belongs to the Tec family of tyrosine kinases, in the cross-talk between the integrin/FAK and the MyD88 pathways in fibroblast-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…A similar study described in synovial fibroblasts a functional and physical interaction of BMX with MyD88 and Mal, components of the LPS signaling pathway (31). In this case, an siRNA against BMX showed inhibition of LPS-induced IL-6 secretion, very similar to our results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar study described in synovial fibroblasts a functional and physical interaction of BMX with MyD88 and Mal, components of the LPS signaling pathway (31). In this case, an siRNA against BMX showed inhibition of LPS-induced IL-6 secretion, very similar to our results.…”
Section: Discussionsupporting
confidence: 81%
“…It has also been demonstrated that BMX is involved in cardiac hypertrophy induced by pressure overload (27) or VEGF-B (28). Furthermore, a role of BMX in TLR signaling and cytokine secretion has been suggested based on its activation by TLR ligands (29)(30)(31). Finally, skin-specific overexpression of BMX has been shown to generate skin hyperplasia and inflammatory angiogenesis (32).…”
mentioning
confidence: 99%
“…[86][87][88] FAK consists of an N-terminal FERM domain, a tyrosine kinase domain, a proline-rich region and a C-terminal FAT domain. The FERM domain interacts with the kinase domain, leading to autoinhibition of FAK.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…89 FAK is involved with TLR-induced MyD88 signaling, which plays a role in initiating innate immune responses. 87 FAK and CD4 have been implicated in a signaling complex in T cells stimulated by the HIV protein gp120. 88 The FAT domain binds to the CD4 endocytosis motif, which limits lymphocyte-specific protein tyrosine kinase binding to CD4.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…Transient transfection of FLS with Clear-MiR miRNA inhibitor (200 nM) and reporter constructs (200 ng/ml) was performed using the human dermal fibroblast Nucleofector kit from Amaxa as previously described (27). Transient transfection of THP-1 cells with miR-346 mimic (200 nM) was performed using the cell line Nucleofector kit V from Amaxa.…”
Section: Transfections and Luciferase Assaymentioning
confidence: 99%